Understanding the coach's role in the development of mental toughness: Perspectives of elite Australian football coaches - Gucciardi, D. F.; Gordon, S.; Dimmock, J. A.; Mallett, C. J. (Journal of Sports Sciences, 2009)
The purpose of this study was to explore elite coaches' perceptions of how they can both facilitate and impede the development of key mental toughness characteristics in the context of Australian football. Eleven coaches from a previous study (Gucciardi, Gordon, & Dimmock, 2008) were re-interviewed and the transcribed verbatim data were analysed using grounded theory data analytical procedures (Strauss & Corbin, 1998). Five categories that appear to be central to the coach's role in the development of mental toughness in Australian football emerged. Four of these categories (coach-athlete relationship, coaching philosophy, training environments, and specific strategies) were said to facilitate the developmental process, whereas the final category (negative experiences and influences) was said to impede this process. A grounded theory in which the aforementioned categories enable coaches to nurture a "generalized form" of mental toughness acquired during one's formative years into a "sport-specific form" pertinent to Australian football is presented. The theoretical and practical implications of these findings are discussed.